Robotic-assisted tendon transplantation—approach for pelvic organ prolapse repair: a case report - Dominique Koensgen; Charlotte Lukannek; Carolin Schroeder; Lucia A. Otten; Amadeus Hornemann; Alexander Mustea (Journal of Medical Case Reports)
Abstract Background The management of pelvic organ prolapse remains a clinical challenge, particularly with concerns regarding the safety of synthetic mesh-based procedures. In response, we present a novel approach for apical prolapse repair utilizing robotic assistance for tendon transplantation, offering a promising alternative to the use of synthetic meshes. Case presentation A 47-year-old multiparous woman (white, non-Hispanic) with a history of three vaginal deliveries and laparoscopic supracervical hysterectomy presented with symptoms of pelvic organ prolapse, including vaginal discomfort, recurrent urinary tract infections, and overactive bladder. Clinical examination and ultrasonography revealed a combined anterior and apical vaginal prolapse grade II according to the Pelvic Organ Prolapse Quantification system. A robotic sacrocervicopexy with a semitendinosus autograft, harvested from the left popliteal fossa, and concomitant anterior colporrhaphy were performed. The surgical procedure included the dissection of the ligamentum longitudinale using a nerve-sparing technique, cervix preparation, and tendon transplantation. The surgery lasted 172 min without intraoperative complications. The patient’s postoperative recovery was swift without residual prolapse, voiding dysfunction, or urinary incontinence reported at any of the follow-up examinations, conducted at 8 weeks, 3 months, 6 months, and 1 year after the operation. Conclusion This case report demonstrates the successful application of a robotic-assisted tendon transplantation approach for apical prolapse repair, offering a safe and effective alternative to synthetic mesh-based surgical procedures. An ongoing multicenter registry study aims to further validate the method’s safety and efficacy, paving the way for its broader adoption in clinical practice.